UPAYA MENINGKATKAN HASIL BELAJAR PASSING ATAS DALAM PERMAINAN BOLA VOLI DENGAN METODE MENGAJAR DEMONSTRAN PADA SISWA KELAS VIII-B SMP NEGERI 39 MEDAN TA 2017/2018 - Arianus Lawolo (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
This study aims to determine the improvement of Upper Passing Learning Outcomes in Volleyball Games with Demonstration Teaching Methods for Class VIII-B Students of SMP Negeri 39 Medan FY 2017-2018. Of the 39 students who took the test, there were 19 students (48.71%) who passed the KKM with a value range of 76-85 and an average score = 80. 28. The results achieved were that all students could pass the KKM with a range of values between 75-77 and an average value of 76. Thus, this study concludes that learning by using the demonstration teaching method can make a very large and significant contribution to the passing ability of volleyball in class VIII-B students of SMP Negeri 39 Medan in the 2017 academic year. /2018.